IMPROVING THE REPRODUCTIVE ABILITY OF THE DAIRY CATTLE - Baimukanov Dastanbek Asylbekovich; Seidaliyev Nurzhan Beskempirovich; Alentayev Aleidar Saldarovich; Abugaliyev Serimbek Kurmanbaiuly; Semenov Vladimir Grigoryevich; Dalibayev Ermek Kurmanbayevich; Zhamalov Bakbergen Seidakhanuly; Muka Shynar Bakytkyzy (Academic Journal of Physical and Chemical Sciences, 2019)
Based on the gynecological monitoring of 341 cows (268 heads of Simmental breed and 73 heads of Red Steppe breed) of the herd of Bagration 2 farm, performed using rectal medical examination and ultrasound diagnostics, it was found that 42 heads, or 12.3%, were with hypo-ovaria, 14 heads, or 4.1% - with a cyst, 37 heads, or 10.8%, - with inflammation of the uterine lining (endometritis). It has been established that among gynecological diseases, in the Simmental breed, hypo-ovaria (78.6%) and cyst (57.1%) are more common, and in the Red Steppe breed - endometritis (51.4%) and ovarian cyst (42.9%). The number of animals with characteristic signs of hypofunction was only 42 heads, which accounted for 12.3% of the total herd, of which, when distributed by age groups, it was found that 32 heads, or 76.2%, of the third calving and older, 6 heads, or 14.3%, - of the second calving, the remaining 4 heads, or 9.5% - of the first calving, i.e. with age, the number of sick cows naturally increases. In the context of breeds, the same age dynamics was noted: with ovarian dysfunction, there are 28 cows of the 3rd calving and older in the Simmental breed or 84.9%, and 4 cows or 44.5% - in the Red Steppe breed. As for cows of the 2nd calving - 4 heads or 12.1%, of the Simmental breed, and 3 heads or 33.3% - of the Red Steppe breed. For the first calving cows, respectively, 1 head or 3.0%, and 2 heads or 22.2%. On the basis of gynecological monitoring, 2 groups of cows were formed: the first group - the control (without disturbances in the reproductive system), the second group - the experimental group (with hypo-ovaria). A total of 82 heads were divided into two groups, of them in the control group 30 heads or 75.0%, of the Simmental breed, and 10 heads or 25.0% - of the Red Steppe breed. In the experimental group, 33 heads or 78.6%, and 9 heads or 21.4%, respectively. When using the first scheme of hormonal stimulation of the estrus in the experimental group of 22 heads, at the end of the treatment, signs of estrus were found in 20 cows, which averaged 90.9%. When applying the second scheme of treatment, of 20 heads of the experimental group, 17 animals have had estrus or 85.0%. In total, as a result of the hormonal treatment of 42 heads of cows with ovarian dysfunction, the sexual cycle was restored, i.e. estrus was revealed followed by artificial insemination in 37 heads, which was 88.1%. When comparing the results of using two schemes of hormonal stimulation, it was found that the use of CIDR increased the fertility of cows by 5.9%. With the use of ultrasound diagnostics in 28 cows (14 heads were repeatedly bred on the natural cycle), the fertility of insemination was 66.7% since their pregnancy was established. When using the hormonal treatment scheme with Fertagil, from 23 cows with a follicular cyst during ultrasound diagnostics on the 10-12 day before PG F-2 α injection, 7 heads showed no ovarian follicular cysts, which is 36.8%. When using the Surfagon drug and ultrasound diagnostics on the 12-14 day before the PG F-2 α injection, the number of cows without signs of follicular cyst in the ovaries was 10 heads or 43.5% of the amount of hormonally treated. According to the results of artificial insemination of treated animals, the fruitfulness from the first insemination was 42.8% in the group treated with Fertagil and 40% in the group treated with Surfagon.